Financial Technology Use in Fulfilling Family Needs: A Maqāṣid al-Sharīʿah Perspective - Dwi Prasetyo; Wargo; Zaenal Abidin (Zabags International Journal of Islamic Studies, 2025)
The proliferation of financial technology (fintech) has reshaped global and national financial systems, including practices within Muslim households in Indonesia. Beyond enabling efficient transactions, fintech holds potential to advance the objectives of Maqāṣid al-Sharīʿah, particularly in ḥifẓ al-māl (protection of wealth). This study examines how fintech is employed as a medium for family financial transactions and assesses its alignment with Maqāṣid al-Sharīʿah principles. Adopting a qualitative phenomenological approach, data were collected through observation, in-depth interviews, and documentation, then analyzed using triangulation techniques. Findings indicate that Muslim families utilize fintech for bill payments, budgeting, and sharia-compliant investments, with varying levels of digital literacy. Fintech demonstrably enhances convenience, security, and efficiency, although challenges persist, including data security risks, limited literacy, and uncertainties regarding Sharia regulatory oversight. The study contributes theoretically by shifting Islamic fintech discourse to the micro-level of households and offers practical implications for designing fintech products that better serve Muslim family needs while supporting clear, sharia-compliant regulatory frameworks.